PERAN KEPUASAN PELANGGAN DALAM MEMEDIASI KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA GONG VANKA GUEST HOUSE CANGGU - I Gede Adi Permana Putra; Anak Agung Putu Agung; Ni Putu Nita Anggraini (VALUES, 2021)
Customer loyalty is a deep commitment of customers for years to re-subscribe or to consistently repurchase selected products or services in the future. Customer loyalty can be affected by service quality and customer satisfaction. This study aims to examine the effect of service quality on customer loyalty which is mediated by customer satisfaction. The data collection method was done by using a questionnaire. The sample in this study were 100 respondents. The sample was determined by using purposive sampling technique, namely the technique of determining the sample with certain considerations or criteria. The data analysis technique used was Partial Least Square (PLS). The results of the instrument test showed valid and reliable data. The results showed that service quality had a positive and significant effect on customer satisfaction with a statistical value of 9,579. Customer satisfaction has a positive and significant effect on customer loyalty with a statistical value of 2.401. Service quality has a positive and significant effect on customer loyalty with a statistical value of 7,320. Customer satisfaction can mediate the effect of service quality on customer loyalty at Gong Vanka Guest House Canggu.